Unit Cell Analysis of the Superelastic Behavior of Open-Cell Tetrakaidecahedral Shape Memory Alloy Foam under Quasi-Static Loading. (8th July 2014) - Maîtrejean, Guillaume; Terriault, Patrick; Devís Capilla, Diego; Brailovski, Vladimir
Abstract : Cellular solid materials and, more specifically, foams are increasingly common in many industrial applications due to their attractive characteristics. The tetrakaidecahedral foam microstructure, which can be observed in many types of foams, is studied in the present work in association with shape memory alloys (SMA) material. SMA foams are of particular interest as they associate both the shape memory effect and the superelasticity with the characteristics of foam. A Unit Cell Finite Element Method approach is used, an approach that allows accurate predicting of the macroscale response of the foam with a highly reduced numerical effort. The tetrakaidecahedral foam's responses, both in the elastic and in the superelastic stages, are then extracted and compared with results from the literature. The tetrakaidecahedral geometry is found to be of particular interest when associated with SMA as it takes more advantage of the superelastic property of the material than foams with randomly distributed porosity.